2002
DOI: 10.1097/00005176-200208000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Endothelin-1 Concentrations in Children With Cirrhosis and Their Relationship to Renal Function and the Severity of Portal Hypertension

Abstract: Plasma ET-1 concentrations are increased in children with cirrhosis, with or without ascites, compared with controls. Patients with cirrhosis and ascites have increased ET-1 concentrations compared with those without ascites. The degree of increase does not relate to the severity of portal hypertension. This increase tends to maintain systemic blood pressure but is associated with a decrease in renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…SPP301 significantly increased plasma ET‐1 levels at the lowest dose of 5 mg. Plasma ET‐1 measurements are useful because plasma concentrations have been found to correlate well with the severity of certain diseases such as primary pulmonary hypertension, cirrhosis, and heart failure 9–11 . The observation that circulations of ET‐1 are increased by the ET A receptor selective antagonist SPP301 in this study is in line with recent observations by others 12 .…”
Section: Discussionsupporting
confidence: 90%
“…SPP301 significantly increased plasma ET‐1 levels at the lowest dose of 5 mg. Plasma ET‐1 measurements are useful because plasma concentrations have been found to correlate well with the severity of certain diseases such as primary pulmonary hypertension, cirrhosis, and heart failure 9–11 . The observation that circulations of ET‐1 are increased by the ET A receptor selective antagonist SPP301 in this study is in line with recent observations by others 12 .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, these studies found increased ET-1 synthesis in the renal papilla, which may contribute to renal dysfunction and predispose to acute renal failure during OJ (12). A clinical study of pediatric patients with cirrhosis showed a negative correlation between plasma ET-1 and creatinine clearance (22), which corroborates the link between renal dysfunction and OJ. In addition, it has been shown that ET-1 induces renal synthesis of PGE 2 , which exerts a vasodilatory effect on renal vascular tone (23).…”
Section: Discussionmentioning
confidence: 62%
“…A recent study found significantly elevated plasma endothelin-1 levels in patients with PPHTN compared to cirrhotic patients with portal hypertension but without pulmonary hypertension [8]. In addition, a large body of evidence suggests that endothelin-1 may also be involved in the pathogenesis of portal hypertension [24][25][26][27][28]. A recent case report of a patient with PPHTN (who was included in the present study) described normalisation of portal venous pressures with bosentan treatment [20].…”
Section: Discussionmentioning
confidence: 62%